2020
DOI: 10.1007/s10899-020-09936-3
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Gambling Behavior: Evidence from Japan

Abstract: According to a survey by Japan's Ministry of Health, Labor, and Welfare in 2017, 3.6% of Japanese adults-equivalent to about 3.2 million people-have suffered from problem gambling at some point in their lifetime. This study examines the relationship between financial literacy, financial education, and gambling behavior (measured as gambling frequency) among the Japanese population. We hypothesize that financially literate and financially educated people who use their knowledge to make sound financial decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 53 publications
10
54
4
3
Order By: Relevance
“…We hypothesize that financial literacy and financial education, which enable people to make rational decisions, reduce the likelihood of being a smoker. Watanapongvanich, Khan, Putthinun, Ono, and Kadoya’s [ 1 ] findings on financial literacy and financial education as rational decision-making instruments support our hypothesis. To the best of our knowledge, this is the first study which addresses the association between financial literacy, financial education, and smoking behavior among the American population.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We hypothesize that financial literacy and financial education, which enable people to make rational decisions, reduce the likelihood of being a smoker. Watanapongvanich, Khan, Putthinun, Ono, and Kadoya’s [ 1 ] findings on financial literacy and financial education as rational decision-making instruments support our hypothesis. To the best of our knowledge, this is the first study which addresses the association between financial literacy, financial education, and smoking behavior among the American population.…”
Section: Introductionsupporting
confidence: 82%
“…A recent study found that financial literacy and financial education significantly impact the smoking behavior in Japan [ 1 ]. The study claims that financially literate and financially educated people, who have the ability to make rational decisions, are less likely to smoke because they rationally value the current pleasure and potential negative consequences of smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire sought to determine the participants’ personal socioeconomic status and risk preferences (Supplemental Table S2 ). The reliability and validity have been established with the general population 12 including those with obesity 13 and smoking. 14 Retinopathy was evaluated and categorized by ophthalmologists via fundoscopy after pupillary dilatation according to the Davis classification as follows: no diabetic retinopathy, simple diabetic retinopathy, preproliferative diabetic retinopathy, and proliferative diabetic retinopathy, including panretinal photocoagulation.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire sought to determine the participants' personal socioeconomic status and risk preferences (Supplemental Table S2). The reliability and validity have been established with the general population 12 including those with obesity 13…”
Section: Dovepressmentioning
confidence: 99%